The Communication Philosophy of the Basiacuong Tradition in Ocu Language Expressions as an Ethnolinguistic Study - Hasnah Faizah; Rahmi Septia Frisye; Nurhasni Nurhasni (International Journal of Studies in International Education, 2025)
The Basiacuong tradition is one of the oral cultural heritages of the Kampar (Ocu) people in Riau, which is rich in philosophical, ethical, and religious values. This study aims to analyze the expressions in the Ocu language that appear in Basiacuong practices using an ethnolinguistic approach. The research data were obtained through audiovisual observations of Basiacuong videos published in digital media, then transcribed and translated into Indonesian. The analysis was carried out using the interactive model of Miles and Huberman (1994) through three stages: data reduction, data presentation, and drawing conclusions. The results of the study indicate the existence of eight main utterances that include proverbs, traditional pantun, advice, religious expressions, and social and philosophical expressions. These utterances function to instill moral values, strengthen social ethics, entertain, and legitimize customs through Islamic teachings. This study confirms that the Basiacuong tradition is not merely an oral performance, but a means of inheriting cultural identity and an educational medium that remains relevant in maintaining social harmony in the Kampar community.